Work-related musculoskeletal injuries in physiotherapists - Emilia Mikołajewska (Nofer Institute of Occupational Medicine, 2013)
The aim of this paper is to present an overview of current knowledge on the work-related musculoskeletal injuries in physiotherapists. The author analyzed the literature data concerning the results of studies published until the first half of 2013. Based on the reviewed literature various causal factors, sources of exposure, and effects of aforementioned injuries are also analyzed and presented. Further strategies to increase health professionals' awareness of the importance of prevention aimed at decreasing the prevalence of aforementioned injuries are required. Med Pr 2013;64(5):681-687